FINTECHS - regulação macro e estrutura micro : as novas tecnologias financeiras ante a ordem econômica e as normas de compliance do sistema bancário brasileiro - Cappellari, Álisson dos Santos (2022)
The present dissertation takes on the task to investigate the genesis and the future perspectives of the movement of change in provision of financial services, so far deemed as the essence of traditional financial institutions, for fintechs, entities that present a disruptive, digital and instantaneous character as well as a minimalist physical structure. This essay will also examine the role that both traditional financial institutions and entities responsible for regulating and inspecting the financial system play in this movement. The hypothetico-deductive approach to the theme, developed by Karl S. Popper, was a methodological path considered effective to conduct the necessary investigations and reach the results obtained in order to seek confirmation of the presented thesis. The typological, structuralist and comparative methods of research were adopted to analyze the central objects of the present paper, which are the fintechs and the regulation of the Brazilian banking system. Therefore, based on the regulatory standards that can be applied to compliance in financial institutions, as well as the analysis of the corporate structure of these new entities, the thesis is believed to have been ratified, reaching the result that the concept of the legal landmark that is historically enforced upon the traditional entities of the National Financial System is not compatible with the technological, minimalist and disruptive nature of fintechs. Although the sector regulation predicts a certain degree of adaptation respecting its application to entities endowed with a less complex structure, taking into account factors such as the institution's nature, size, complexity, structure, risk profile and business model, regarding specifically the demands of compliance programs to be adopted by fintechs, they remain inconsistent with the goal pursued by the supervisor entity.